FORECASTING METHODS DETERMINATION OF RAW MATERIAL REQUIREMENTS FOR SHEEP CABRETTA AND BATTING LEATHER AT PT ADI SATRIA ABADI - Khairun Nadiyah; Grita Supriyanto Dewi (Journal of Industrial Engineering and Halal Industries, 2022)
The high level of fluctuating demand for products that consumers want, makes companies need to have a demand estimation or forecasting tool. PT. Satria Abadi is a manufacturing company engaged in the leather tanning process. Leather processed by PT. Adi Satria Abadi consists of two types of leather, namely goat skin (Goat Cabretta and Goat Batting) and sheep skin (Sheep Cabretta and Sheep Batting). In the tanning process, PT. Adi Satria Abadi sometimes encounters several obstacles, one of which is insufficient raw materials. This is because there has not been an estimate of the need for raw materials for the production process to fulfil demand. To deal with these obstacles, it is necessary to estimate the need for raw materials for the type of Sheep Cabretta Leather and Sheep Batting Leather so that there is no shortage of raw materials that can hinder the leather tanning production process. Based on the pattern of demand for raw materials, Sheep Cabretta Leather and Sheep Batting Leather are included in a random or fluctuating demand pattern. Therefore, the method used to predict the need for raw materials is Single Exponential Smoothing with 0.1 to 0.9. From the results of the calculation of forecasting accuracy, it was found that the smallest MSE value lies in the results of forecasting with the Single Exponential Smoothing method with an alpha value of 0.7 of 44560919259, while in sheep Batting Leather, it also lies in the Single Exponential Smoothing forecasting with an alpha of 0.7 with an MSE value amounting to 31462955201. Therefore, the need for raw materials for the type of Sheep Caretta Leather for June based on forecasting calculations using the Single Exponential Smoothing method with an alpha value of 0.7 is 964,878.62 SF, while for the need for raw materials for the type of Sheep Batting Leather is 989,018.39 SF.